Antitumor effects of novel compound, guttiferone K, on colon cancer by p21Waf1/Cip1‐mediated G0/G1 cell cycle arrest and apoptosis. Issue 3 (11th July 2012) - Kan, Winnie Lai Ting; Yin, Chun; Xu, Hong Xi; Xu, Gang; To, Kenneth Kin Wah; Cho, Chi Hin; Rudd, John Anthony; Lin, Ge
Abstract Low selectivity is one of the major problems of currently used anticancer drugs, therefore, there is a high demand for novel, selective antitumor agents. In this study, the anticancer effects and mechanisms of guttiferone K (GUTK), a novel polyprenylated acylphloroglucinol derivative isolated from Garcinia cowa Roxb., were examined for its development as a novel drug targeting colon cancer. GUTK concentration‐ and time‐dependently reduced the viability of human colon cancer HT‐29 cells (IC50 value 5.39 ± 0.22 μM) without affecting the viability of normal human colon epithelial CCD 841 CoN cells and induced G0/G1 cell cycle arrest in HT‐29 cells by down‐regulating cyclins D1, D3 and cyclin‐dependent kinases 4 and 6, while selectively restoring p21Waf1/Cip1 and p27Kip1 to levels comparable to those observed in normal colon cells, without affecting their levels in normal cells. GUTK (10.0 μM) induced cleavage of PARP, caspases‐3, ‐8 and ‐9 and chromatin condensation to stimulate caspase‐3‐mediated apoptosis. The addition of a JNK inhibitor, SP600125, partially reversed GUTK‐induced caspase‐3 activity, indicating the possible involvement of JNK in GUTK‐induced apoptosis. Furthermore, GUTK (10 mg/kg, i.p.) significantly decreased the tumor volume in a syngeneic colon tumor model when used alone or in combination with 5‐fluorouracil without toxicity to the mice. Immunohistochemical staining of the tumor sections revealed a mechanism involving an increase in cleaved caspase‐3 and a decrease in cell proliferation marker Ki‐67. Our results support GUTK as a promising novel, potent and selective antitumor drug candidate for colon cancer.